Decompression alone versus decompression with limited fusion for treatment of degenerative lumbar scoliosis in the elderly patient - Daubs, Michael D; Lenke, Lawrence G; Bridwell, Keith H; Cheh, Gene; Kim, Yongjung J; Stobbs, Georgia (Evidence-Based Spine-Care Journal, 2012)
Study design: Retrospective cohort study.Objective: To analyze the surgical results of a group of patients older than 65 years treated for mild degenerative lumbar scoliosis (<30°) with stenosis, treated with decompression alone or decompression and limited fusion.Methods: We evaluated 55 patients, all older than 65 years from our prospectively collected database with mild degenerative scoliosis (<30°) and stenosis who underwent surgery. Laminectomy alone was performed in 16 patients, and laminectomy and limited fusion in 39 patients. Mean follow-up was 4.6 years in the decompression group and 5.0 years in the fusion group. Clinical results were graded by patients’ self-reported satisfaction and length of symptom-free period to recurrence.Results: In the decompression alone group, 6 (37%) of 16 patients developed recurrent stenosis at the previously decompressed level and five developed recurrence within 6 months postoperatively versus the decompression and fusion group where 3 (8%) of 39 (P = .0476) developed symptomatic stenosis supra adjacent to the fusion. Of 16 patients in the decompression alone group, 12 (75%) had recurrence of symptoms by the 5-year follow-up period versus only 14 (36%) patients in the decompression and fusion group (P = .016). Adjacent segment degenerative changes were common in the fusion group, but only 7% developed symptomatic stenosis.Conclusions: Decompression with limited fusion prevents early return of stenotic symptoms compared with decompression alone in the setting of mild degenerative scoliosis (<30°) and symptomatic stenosis in patients 65 years and older.The definiton of the different classes of evidence is available here.